2015 17th International Conference on E-Health Networking, Application &Amp; Services (HealthCom) 2015
DOI: 10.1109/healthcom.2015.7454588
|View full text |Cite
|
Sign up to set email alerts
|

On effectiveness of lossless compression in transferring mHealth data files

Abstract: Abstract-The health and fitness data traffic originating on mobile devices has been continually increasing, with an exponential increase in the number of personal wearable devices and mobile health monitoring applications. Lossless data compression can increase throughput, reduce latency, and achieve energyefficient communication between personal devices and the cloud. This paper experimentally explores the effectiveness of common compression utilities on mobile devices when uploading and downloading a represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The effective upload and download throughputs and energy efficiencies depend on many factors, including the file size and type, selected compression utility, the compression level, network characteristics such as latency and throughput, as well as the smartphone's performance and energyefficiency. Whereas previous studies showed that compressed uploads and downloads can save time and energy in many typical file transfers initiated from smartphones Dzhagaryan and Milenkovic, 2015;Milenkovic et al, 2013b) there is not a single upload or download file transfer method that works the best for all data types and network conditions. To underscore this problem, we conduct a measurement-based study that evaluates the effectiveness of various data transfer options under different network conditions.…”
Section: File Transfers In Mobile Cloudmentioning
confidence: 96%
“…The effective upload and download throughputs and energy efficiencies depend on many factors, including the file size and type, selected compression utility, the compression level, network characteristics such as latency and throughput, as well as the smartphone's performance and energyefficiency. Whereas previous studies showed that compressed uploads and downloads can save time and energy in many typical file transfers initiated from smartphones Dzhagaryan and Milenkovic, 2015;Milenkovic et al, 2013b) there is not a single upload or download file transfer method that works the best for all data types and network conditions. To underscore this problem, we conduct a measurement-based study that evaluates the effectiveness of various data transfer options under different network conditions.…”
Section: File Transfers In Mobile Cloudmentioning
confidence: 96%
“…When a file is decompressed, lossless compression keeps the original file's quality. It is documented that lossless compression is used [2][3][4][5][6]. In this work, to remove the unnecessary portions that need a large amount of memory of digital photographs, the statistical technique is utilized for this task.…”
Section: Introductionmentioning
confidence: 99%